Deletion of S-Layer Associated Ig-Like Domain Protein Disrupts the Lactobacillus acidophilus Cell Surface - Klotz, Courtney; Goh, Yong Jun; O’Flaherty, Sarah; Johnson, Brant; Barrangou, Rodolphe (Frontiers in Microbiology, 2020)
Bacterial surface-layers (S-layers) are crystalline arrays of repeating proteinaceous subunits that coat the exterior of many cell envelopes. S-layers have demonstrated diverse functions in growth and survival, maintenance of cell integrity, and mediation of host interactions. Additionally, S-layers can act as scaffolds for the outward display of auxiliary proteins and glycoproteins. These noncovalently-bound S-layer associated proteins (SLAPs) have characterized roles in cell division, adherence to intestinal cells, and modulation of the host immune response. Recently, IgdA (LBA0695), a Lactobacillus acidophilus SLAP that possesses a Group 3 immunoglobulin (Ig)-like domain and GW (Gly-Tryp) dipeptide surface anchor, was recognized for its high conservation among S-layer-forming lactobacilli, constitutive expression, and surface localization. These findings prompted its selection for examination within the present study. Although IgdA and corresponding orthologs were shown to be unique to host-adapted lactobacilli, the Ig domain itself was specific to vertebrate-adapted species suggesting a role in vertebrate adaptation. Using a counterselective gene replacement system, igdA was deleted from the L. acidophilus NCFM chromosome. The resultant mutant, NCK2532, exhibited a visibly disrupted cell surface which likely contributed to its higher salt sensitivity, severely reduced adhesive capacity, and altered immunogenicity profile. Transcriptomic analyses revealed the induction of several stress response genes and secondary surface proteins. Due to the broad impact of IgdA on the cellular physiology and probiotic attributes of L. acidophilus, identification of similar proteins in alternative bacterial species may help pinpoint next-generation host-adapted probiotic candidates.